India's Multilayered West Asia Policy: A Comparative Study of Strategic Partnerships with Palestine and Israel : भारत की बहुस्तरीय पश्चिम एशिया नीति: फिलिस्तीन और इजराइल से रणनीतिक साझेदारी का तुलनात्मक अध्ययन - Singh, Rupak Kumar (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
This research paper analyzes the seemingly contradictory yet strategically balanced nature of India’s West Asia policy, wherein India has historically supported Palestine’s right to self-determination and independence, while simultaneously strengthening its military, technological, and economic partnership with Israel. The study highlights how India, while upholding its non-aligned and moral values, maintains relations with both parties through a pragmatic realist approach. It examines how India’s foreign policy manages to support the ‘Two-Nation Theory,’ vote in favor of Palestine at the United Nations, and sustain ties with Arab countries, while deepening its cooperation with Israel in defense, water, and agricultural technologies. This delicate balance positions India as a responsible global power that not only protects national interests but also plays a role in providing moral global leadership. India’s multilayered policy reflects diplomatic flexibility and also helps it address critical challenges such as energy security, the safety of overseas Indians, and counter-terrorism. Abstract in Hindi Language: यह शोध-पत्र भारत की पश्चिम एशिया नीति के अंतर्विरोधी लेकिन रणनीतिक रूप से संतुलित स्वरूप का विश्लेषण करता है, जिसमें एक ओर भारत ने ऐतिहासिक रूप से फिलिस्तीन के आत्मनिर्णय और स्वतंत्रता का समर्थन किया है, वहीं दूसरी ओर इजराइल के साथ सैन्य, तकनीकी और आर्थिक साझेदारी को सुदृढ़ किया है। शोध में यह स्पष्ट किया गया है कि भारत किस प्रकार अपने गुटनिरपेक्ष और नैतिक मूल्यों को कायम रखते हुए एक प्रायोगिक यथार्थवादी नीति के तहत दोनों पक्षों से संबंध बनाए रखता है। भारत की विदेश नीति कैसे ‘दो-राष्ट्र सिद्धांत’ के समर्थन, संयुक्त राष्ट्र में फिलिस्तीन के पक्ष में मतदान, और अरब देशों से संबंध बनाए रखते हुए, इजराइल से रक्षा, जल और कृषि तकनीक के क्षेत्र में गहरे होते सहयोग को साधती है। यह संतुलन भारत को एक उत्तरदायी वैश्विक शक्ति के रूप में प्रस्तुत करता है जो न केवल राष्ट्रीय हितों की रक्षा करता है, बल्क़ी नैतिक वैश्विक नेतृत्व की भी भूमिका निभाता है। भारत की यह बहुस्तरीय नीति न केवल कूटनीतिक लचीलापन दर्शाती है, बल्कि उसे ऊर्जा सुरक्षा, अप्रवासी भारतीयों की सुरक्षा और आतंकवाद-निरोध जैसी चुनौतियों से निपटने में मदद भी प्रदान करती है। Keywords: भारत की विदेश नीति, पश्चिम एशिया, इजराइल-भारत संबंध, फिलिस्तीन नीति, रणनीतिक साझेदारी